(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
There is a need to teach subject matter reasoning in the science classroom. Science is a process, and unfortunately many students do not understand the process of science. Traditionally science has been taught as a list of discoveries to be memorized and regurgitated. Teaching subject matter reasoning takes the inquiry approach to education. Inquiry is stated as a requirement by the National Science Education Standards, and by many state science standards. The most studied approach to inquiry education is project-based learning. Students are taught subject matter reasoning through using skills necessary to be successful in a project-based learning (PBL) classroom. PBL takes a great deal of planning and investment on the teachers’ part, but the benefits to the students’ knowledge and reasoning skills are more than worth the time and effort put in on the teachers’ part.